Nano-Scale Smoothing of Double Layer Porous Si Substrates for Detaching and Fabricating Low Cost, High Efficiency Monocrystalline Thin Film Si Solar Cell by Zone Heating Recrystallization. (5th January 2017) - Takazawa, Chiaki; Fujita, Makoto; Hasegawa, Kei; Lukianov, Anatolii; Zhang, Xiaomei; Noda, Suguru; Ihara, Manabu
Abstract : A fabrication process of monocrystalline thin films for Si solar cells was developed that uses epitaxial growth and layer transfer process for low fabrication cost and high photoelectric conversion efficiency. Fabrication of high crystalline epitaxial thin films requires controlling the surface roughness and pore size of the seed layer in nano-level, double layer porous Si (DLPS). By using this zone heating recrystallization (ZHR) method, in which the top surface of DLPS is selectively annealed by scanning upper lamp heater, we successfully reduced the surface roughness and pore size. By using the rapid vapor deposition (RVD) method, we fabricated an epitaxial monocrystalline Si thin film in 1 min on the ZHR-treated DLPS and then easily detached this thin film from the substrate. The crystal distortion of epitaxial Si thin films can be controlled by using ZHR to smooth and change only the top surface of DLPS.